HUBUNGAN KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH DENGAN KOMITMEN KERJA GURU DI SMP NEGERI SE-KECAMATAN NANGGALO - Sintya Permata Herlya; Nellitawati; Irsyad; Nikmah Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the author's observations, which showed that teachers' work commitment at public junior high schools in the Nanggalo subdistrict was still less than optimal. One of the contributing factors was the instructional leadership of the school principals. The purpose of this study is to determine the relationship between the instructional leadership of school principals and teacher commitment at public junior high schools in Nanggalo District. The method used is quantitative with a correlational research design. The population of this study consists of teachers at public junior high schools in Nanggalo District, totaling 149 individuals. The research sample was taken using the Proportional Stratified Random Sampling technique with the Chocran formula, resulting in a sample size of 64 people. Data collection used a Likert scale questionnaire that had been tested for validity and reliability. Data analysis techniques used Pearson's correlation analysis with the help of the SPSS version 26 For Windows program. The results of the study show that: 1) The work commitment of teachers at public junior high schools in the Nanggalo subdistrict has been implemented very well, with an average score of 4.79. 2) The instructional leadership of principals at public junior high schools in the Nanggalo subdistrict has been implemented very well, with an average score of 4.76. 3) There is a significant relationship between the instructional leadership of the principal and teacher work commitment, with a correlation coefficient of 0.564 and a correlation significance test showing 5.377 > 1.670 at a significance level of 5% or a confidence level of 95%. Based on the results of this study, it can be concluded that there is a significant relationship between the instructional leadership of the principal and teacher work commitment at SMP Negeri Se-Kecamatan Nanggalo.